2016
DOI: 10.1155/2016/3968206
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Circulating MicroRNAs Levels during the Switch from Clopidogrel to Ticagrelor

Abstract: Background. Circulating microRNAs are appealing biomarkers to monitor several processes underlying cardiovascular diseases. Platelets are a major source for circulating microRNAs. Interestingly, the levels of specific microRNAs were reported to correlate with the level of platelet activation. The aim of the present study was to test whether the treatment with the novel antiplatelet agent, ticagrelor, is associated with modulation in the levels of key platelet-derived microRNAs. Methods and Results. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 20 publications
5
54
0
2
Order By: Relevance
“…As illustrated in Figure 1, cessation of clopidogrel, prasugrel and ticagrelor led to a significant increase in ADP-mediated platelet aggregation measured by MEA, as one would expect. 22 Furthermore, Willeit and colleagues showed that the administration of a loading dose of prasugrel alters the expression of miRNA-126, -150, -191, -223 and -24 in healthy volunteers and patients with symptomatic carotid atherosclerosis. This is against our expectations based on previous studies: Carino et al found a significant reduction in miRNA-126, -223 and -150 after switching from clopidogrel to prasugrel in 16 patients with acute coronary syndrome and an increase in the levels of miRNA-96.…”
Section: Clopidogrel Prasugrel Ticagrelormentioning
confidence: 99%
See 3 more Smart Citations
“…As illustrated in Figure 1, cessation of clopidogrel, prasugrel and ticagrelor led to a significant increase in ADP-mediated platelet aggregation measured by MEA, as one would expect. 22 Furthermore, Willeit and colleagues showed that the administration of a loading dose of prasugrel alters the expression of miRNA-126, -150, -191, -223 and -24 in healthy volunteers and patients with symptomatic carotid atherosclerosis. This is against our expectations based on previous studies: Carino et al found a significant reduction in miRNA-126, -223 and -150 after switching from clopidogrel to prasugrel in 16 patients with acute coronary syndrome and an increase in the levels of miRNA-96.…”
Section: Clopidogrel Prasugrel Ticagrelormentioning
confidence: 99%
“…13,22 Moreover, our patients were followed for 6 months at 4 different time points and the investigated miRNA were predefined at the beginning of the study. All patients received optimal contemporary concomitant pharmacological treatment and last generation drug-eluting stents and, therefore, represent a relevant, well-treated cohort of stable CAD patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In fact, several studies reported an association between circulating levels of specific miRNAs and cardiovascular diseases, including acute myocardial infarction, 5,6 myocarditis, 7 takotsubo syndrome, 8 acute and chronic HF, 9 stable coronary artery disease, 10,11 in-stent restenosis, 3,11,12 type 2 diabetes, 13 or in association with different levels of platelet activity. 14 Importantly, since specific miRNAs are differentially expressed in different cell types, circulating levels of specific miRNAs might reflect different biological alterations, which could provide useful hints to the underlying aetiopathogenesis. 15 In this context, we evaluated the transcoronary expression gradients of selected circulating miRNAs in HF patients, to investigate whether a specific release from the heart could be found for different aetiologies underlying HF.…”
Section: Introductionmentioning
confidence: 99%